Improving student’s marine literacy and science process skills through STEM-based discovery learning - Uswatun Khasanah Arifin; S. Supriyatin; Hanum Isfaeni (Universitas Muhammadiyah Malang, 2025)
To bring out science process skills and marine literacy, a learning model that is oriented towards an integrated scientific approach is needed, namely the STEM-based discovery learning model. The purpose of this study is to improve marine literacy skills and science process skills through the STEM-based discovery learning model. The study was conducted from September 2023 to January 2025 at Islamic Senior High School (MAN) 2 of Indramayu. The study was conducted in the even semester of 2023/2024. The study's population was the science department, with 64 students in class X who studied the ecosystem material. The instruments used were essay questions, performance assessments, and STEM-based discovery implementation assessments. The data was analyzed descriptively and quantitatively, and using the MANOVA test. The results of the study on marine literacy skills and science process skills had significant differences between the groups tested. The application of the STEM-based discovery learning model in this study had a significant effect. The findings in this study make learning activities more active because they integrate STEM. The investigation process to obtain knowledge based on the field is included in constructivism. Students not only listen to the teacher's explanation but are involved in problem-solving and investigation activities.